A CASE REPORT OF ADAMS-STOKES SYNDROME - COMPLETE ATRIOVENTRICULAR BLOCK MANIFESTED AS CARDIAC SYNCOPE - Janković, Tamara; Đorđević, Stefan (Halo 194 Scientific Journal of Emergency Medicine, 2025)
INTRODUCTION/OBJECTIVE Syncope is a sudden and transient loss of consciousness caused by brain hypoperfusion.Adams-Stokes syndrome is an arrhythmia manifested by cardiogenic syncope.It is diagnosed easily,by electrocardiographic recording,where a complete AV block is usually observed,often second-degree AV block with a slow ventricular response.The objective is to present a patient in whom syncope happened after physical therapy,while the cause of syncope as part of ASS,was complete AV block.CASE REPORT The patient,74 years old,states that,after getting off the bus,she felt weakness and fainting.She lost consciousness and fell and suffered a head injury.On examination,she was conscious,hypotensive,bradycardic.Electrocardiography registered complete AV block with ventricular response 24/min and complete RBBB.CONCLUSION Considering that unrecognized ASS can lead to serious complications and even sudden cardiac death,it is necessary to standardize the prehospital ECG recording in every patient who clinically presents with syncope or convulsions.
Keywords: adams-stokes syndrome, syncope, bradicardia, complete AV block